Design, Construction and Testing of Freeze Concentrator - Shamsudin, Rosnah (2000)
The main aspects of this study, were the design, construction and performance of a freeze concentrator. The design process consists of three main parts: a vertical tube heat exchanger, an auger to scrape the ice formed and a refrigeration unit to bring the temperature to below freezing. Basically, the freeze concentration process used involves ice formation from a juice solution at the surface of a vertical tube heat exchanger. The ice will be scraped by a rotating auger, which pushes it out through a window and collected in a reservoir. This results in a product of higher solute concentration than its concentration in the feed. The potential application of the freeze concentrator was experimented using sugar solutions at three different feed concentrations i.e. 7.5%, 10.3% and 12% brix, as well as pineapple juice at 11.4% brix. The freezing point depression for the solutions were respectively -l.O7°C, -l.15°C, -1.49°C and -1.49°C. The feed flow rates used for the solutions were respectively 0.65 Vmin, 0.5 Vmin, 0.43 Vmin and 0.45 Vmin. Using these process parameters, the total mass of ice after 180 min is 1.75kg for a feed of 7.5% brix and 1.46kg for a feed of 12% brix. From theoretical analysis, the expected total mass of ice produced is 2.6kg for the 7.5% brix and 1.97kg for the 12% brix solution. Therefore, the performance efficiency for the freeze concentrator is around 67% of theory for all three sugar solutions. Base on the heat balance analysis, the overall thermal performance of this freeze concentration process for the three different feed concentrations shows that about 80010 of the refrigeration load is loss. If these losses were not considered, about 87% of the cooling energy transferred is for sensible heat removal and 13% for ice formation.